The cross-cultural training needs of football coaches - Borges, M.; Rosado, A.; Lobinger, B.; Freitas, F.; de Oliveira, R. F. (International Sport Coaching Journal, 2024)
The ability to interact and communicate effectively in different cultural contexts has never been more relevant for football coaches because cultural diversity in football has increased in the past decades. Yet, there is a reduced number of institutions that are currently offering cultural training to coaches, and it is unknown whether coaches feel the need for such training. This study aimed to explore the cross-cultural training needs of 115 football coaches with national and/or international experience (M = 13.4 years; SD = 8.53). To maximise recruitment reach, an online survey with open-ended questions was used followed by a qualitative thematic analysis. There were four master themes: cross-cultural training needs in the global football market; cross-cultural awareness is important in football; football-specific cultural training; and training by migrant coaches, no matter how. Most coaches perceived a benefit from cultural training in preparation for international appointments, but some felt that coaches already had cultural awareness because they manage individuals and adjust easily to different cultures. Preferences were shown for cross-cultural training delivered by migrant coaches and with a football-specific focus. This is the first study to explore the perceptions of football coaches about cross-cultural awareness and training needs and provides insights to providers of coach education.